IMPLEMENTASI PERMAINAN-PERMAINAN EDUKATIF BAGI ANAK-ANAK BERKEBUTUHAN KHUSUS: STUDI KASUS DI SMP-LB FINJIL KOTA BITUNG - TIMBAN, CHRISTI IRJASARI; Tulung, Golda J.; Warouw, Maya P. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
IMPLEMENTASI PERMAINAN-PERMAINAN EDUKATIF BAGI ANAK-ANAK BERKEBUTUHAN KHUSUS: STUDI KASUS DI SMP-LB FINJIL KOTA BITUNGChristi I. Timban[1]Golda J. Tulung[2]Maya P. Warouw[3]Â ABSTRACTÂ The research is entitled â€œImplementasi Permainan-permainan Edukatif Terhadap Anak-anak Berkebutuhan Khusus: Studi Kasus di SMP-LB Finjil Kota Bitungâ€. The educational games that are used in this research are Bingo alphabet, Charades, and Weather Exchange board game.This research is aimed at: (1) describing the implementation of the educational games and how they influence the students according to Bloomâ€™s taxonomy, (2) finding and analyzing the effects that emerge during the implementation of the games based on studentsâ€™ reactions and teacherâ€™s opinion. The writer uses Case Study method to describe deeply about the implementation of these three games in SMP-LB Finjil kota Bitung. Furthermore, the writer tries to discover the phenomenon in implementing the educational games that include bingo alphabet, charades, and exchange weather board game in SMP-LB Finjil kota Bitung.The findings of this research are: (1) the students can enhance their English skills integratedly through the educational games; (2) these three educational games have some values that are suitable in Bloomâ€™s taxonomy that make these games more decent to be brought as the media of English lesson in the class for students with special needs; (3) there are some themes that emerge through the implementation of the games. First, the learning style that fit the students: kinesthetic and audio style. Second, the motivation and studentâ€™s background that affect the progress of each students. Finaly, one component that can preserve the students to keep engaging during the lesson is giving the reward as the form of the appreciation to the students.Â Â Keywords: Educational games, learning style, children with special needs[1] Mahasiswa yang bersangkutan[2] Dosen Pembimbing Materi[3] Dosen Pembimbing Teknik